PENGARUH PROFITABILITAS, INVENTORY INTENSITY, DAN LEVERAGE TERHADAP AGRESIVITAS PAJAK - Safitri Nur Inayah, (2020)
This research aim to determine the influence of profitability, inventory intensity, and leverage on tax aggressiveness. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange in the range of 2016-2018. Sampling was done by purposive sampling method. The criteria set include companies that publish complete financial statements in the year of observation, the financial statements are presented in Rupiah, and the company is not declared to have suffered losses either in accounting or in fiscal terms. The number of samples used in this study amounted to 176 samples. The analysis technique used is multiple linear regression model with a significance level of 5% and using the IBM SPSS version 25. The results of this research indicate that profitability and leverage do not significantly influence tax aggressiveness. While inventory intensity significantly influences tax aggressiveness.